Estimation of individual crossbreeding effects and growth curve analysis for growth traits of Dorper x Local crossbred sheep in Ethiopia - Besufkad, S.; Abebe, A.; Tesema, Z.; Bisrat, A.; Goshme, S.; Zewdie, T.; Yitagesu, E.; Aydefruhm, D.; Ayele, F.; Demis, C.; Alimenew, E.; Asfaw, T.; et al. (Elsevier, 2025)
Growth data collected from 2011 to 2024 at Debre Birhan Agricultural Research Center sheep breeding station in Ethiopia was used to estimate crossbreeding parameters and describe the growth pattern of Dorper × Menz crossbred sheep. To estimate crossbreeding parameters, the coefficient of breed additive, heterosis and recombination effects in the lamb were fitted as covariates in the analysis. Growth curve model parameters were estimated using Levenberg-Marquardt’s iterative algorithm through the nonlinear regression (NLIN) procedure in SAS. Menz sheep were consistently lighter and gained lower weight than Dorper and their crosses. Relative to the mean value of Menz sheep, the Dorper additive contribution to the BWT, WWT, SMWT, YWT, ADG1, ADG2 and ADG3 of lambs were 47.4, 49.7, 53.4, 63.9, 49.7, 36.9 and 1.16% higher, respectively. The heterosis effects were significantly negative (P<0.05) for BWT, WWT, SMWT and ADG1, but positive (P<0.01) for YWT, ADG2 and ADG3. The estimates of the recombination loss were positive in all traits except for ADG2. The Brody model provided the best fit of growth curve in all lamb genotypes, males, females, single and twin. The present study confirmed that the breed differences, heterosis and recombination effects are important genetic factors affecting growth performance in the Dorper × Menz crossbreeding programs. Moreover, improvement of growth curve parameters could be possible through selection program and intervention of improved management during weaning to six months of age. Therefore, developing an improved management and selection strategy to achieve the desired shape of growth would be very important.